Implementation and Effectiveness of The Simultaneous Reading Culture Program: A Case Study at Politeknik Teknik Kimia Industri (PTKI) Medan Library - Sitanggang, Marianna; Tarigan, Sri Kumala Putri (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2024)
Introduction. It is hoped that the simultaneous reading culture program in tertiary institutions will encourage the academic community to better understand and appreciate the importance of a reading culture and raise awareness of the positive benefits derived from reading habits. A simultaneous reading culture program has been implemented at PTKI Medan which was initiated by the PTKI Medan Library and supported by the Director of PTKI Medan. Reading culture is an important aspect in the academic world, especially in the higher education environment. However, nowadays, the culture of reading in college is often ignored and even considered trivial. Research purposes. The purpose of this study was to find out how much interest, effectiveness and reading habits among the PTKI Medan academic community, encourage the entire academic community to read more, improve the quality of education on campus and introduce the academic community, especially students, to activities that are useful so as to build minds critical and creative. Research methods. This research uses a descriptive qualitative method, with a case study approach. Data collection was carried out using observation, survey and document search methods. Research result. The results of the study showed that the percentage of those who carried out a simultaneous reading culture in PTKI Medan was 77%. However, there are still 23% of users who have never carried out a reading culture simultaneously. Conclusion. From the simultaneous reading culture program that has been carried out within the PTKI Medan environment, it can increase interest in reading and knowledge of students, lecturers and staff as well as create a more cultured and knowledgeable academic environment. This can open opportunities and opportunities for the entire academic community to develop themselves. In addition, this program can also be a good example for other campuses in Indonesia to carry out similar activities.       A B S T R A K       Implementasi dan Efektivitas Program Budaya Membaca Serentak di PTKI (Politeknik Teknologi Kimia Industri) Medan: Studi Kasus di Perpustakaan PTKI Medan. Pendahuluan. Program budaya membaca serentak di perguruan tinggi, diharapkan mendorong civitas akademika untuk lebih memahami dan mengapresiasi pentingnya budaya membaca serta menumbuhkan kesadaran akan manfaat positif yang diperoleh dari kebiasaan membaca. Program budaya membaca serentak telah diimplementasikan di PTKI Medan yang diinisiasi oleh Perpustakaan PTKI Medan dan didukung oleh Direktur PTKI Medan. Budaya membaca adalah salah satu aspek penting dalam dunia akademis, khususnya di lingkungan perguruan tinggi. Namun, saat ini, budaya membaca di perguruan tinggi seringkali diabaikan bahkan dianggap sepele. Tujuan Penelitian. Tujuan penelitian ini adalah untuk mencari tahu seberapa besar minat, efektivitas dan kebiasaan membaca di kalangan civitas akademika PTKI Medan, mendorong seluruh civitas akademika untuk membaca lebih banyak lagi, meningkatkan kualitas pendidikan di kampus dan memperkenalkan civitas akademika khususnya mahasiswa pada kegiatan yang bermanfaat sehingga membangun pikiran kritis dan kreativitas.  Metode Penelitian. Penelitian ini menggunakan metode penelitian survei. Responden adalah pemustaka Perpustakaan PTKI Medan seperti mahasiswa, dosen/pegawai PNS/pegawai non-PNS dan petugas keamanan/kebersihan. Hasil Penelitian. Hasil penelitian menunjukkan bahwa persentase yang melakukan budaya membaca serentak di lingkungan PTKI Medan sebanyak 77%. Namun masih ditemukan 23% pemustaka yang tidak pernah melakukan budaya membaca serentak.  Kesimpulan. Dari program budaya membaca serentak yang telah dilakukan di lingkungan PTKI Medan dapat meningkatkan minat baca dan pengetahuan mahasiswa, dosen dan staf serta terciptanya lingkungan akademik yang lebih berbudaya dan berpengetahuan. Hal ini dapat membuka peluang dan kesempatan bagi seluruh civitas akademika untuk mengembangkan diri. Selain itu, program ini dapat menjadi contoh baik bagi perguruan tinggi lain di Indonesia untuk melaksanakan kegiatan serupa.